Material de enseñanza para escritura creativa de cuentos para tercero de Primaria (2018)
While the pedagogical practice of the Spanish Language degree was developed in the Colombo Florida Bilingual School, it was evidenced a problem about the methods of the creative writing teaching, as the persistence of strong structures in the production of tales and the disconnection between these practices and the communicative needs of children. In consequence, students develop apathy to writing from students, who show a lack of interest when this kind of activities are proposed.